PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, DIVIDEN, PERTUMBUHAN PERUSAHAAN, FREE CASH FLOW DAN PROFITABILITAS TERHADAP KEBIJAKAN HUTANG PERUSAHAAN - RIZKA PUTRI INDAHNINGRUM; RATIH HANDAYANI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2009)
The purpose of this study was to investigate the insider ownership, institutional investor, dividend payments, firm growth, profitability and free cash flow to corporate debt policy. This research uses sample of 31 manufacturing firms and non manufacturing firms, except financial firms which listed in Indonesia Stock Exchange selected using purposive sampling method. The criteria of purposive sampling method are that manufacturing and non manufacturing firms that have been listed in Indonesia Stock Exchange from 2005 until 2007. These firms have reported financial statement every year during year period 2005 until 2007 with fiscal year ending 31 December, get profit and have dividend payout ratio. The statistical methods used in this research are multiple regressions. The result shows that insider ownership, dividend payments and firm growth variable does not have influence towards debt policy. In the other hand, institutional investor, profitability and free cash flow have influence toward debt policy.